Efektivitas Ekstrak Etanol Umbi Decalobanthus mammosus (Lour.) A.R.Simões & Staples Terhadap Makrofag Paru dan Hati Mencit yang Diinduksi Mycobacterium tuberculosis: The Effectiveness of Ethanol Extract Decalobanthus mammosus (Lour.) A.R.Simões & Staples Tubers Against Mycobacterium tuberculosis Induced Lung and Liver Macrophages in Mice - Evy Diah Woelansari; Win Darmanto; Firli Rohmah Primula Dewi; Khambali Khambali (Amerta Nutrition, 2026)
Background: Tuberculosis (TB) cases in Indonesia rank third in the highest number of cases. Incomplete TB treatment causes drug resistance. Ethanol extract of Decalobanthus mammosus (Lour.) A.R.Simões & Staples, tubers has the potential as an immunomodulator and antibacterial. Objectives: This research purpose to decide potency of ethanol essence of Decalobanthus mammosus (Lour.) A.R.Simões & Staples tubers on lung and liver macrophage cells in mice induced by Mycobacterium tuberculosis. Methods: Laboratory experimental research using posttest only with control group. The research sample using Mus muculus mice was divided into control and experimental groups, with the administration of extract doses of 50 mg/kgBW, 100 mg/kgBW and 150 mg/kgBW, and injection of Mycobacterium tuberculosis. Result: The results showed that Decalobanthus mammosus extract dose of 150 mg/kgBW, macrophages were able to overcome Mycobacterium tuberculosis infection, with the lowest number of necrotic cells in the lungs. activation of liver macrophages increased at a dose of 50 mg/kgBW extract. Conclusions: There are differences in macrophages between the liver and lungs. Ethanol Extract of Decalobanthus mammosus (Lour.) A.R.Simões & Staples Tubers on lung macrophage cells, the frequency of macrophage activity is much higher compared to the liver.